2001
DOI: 10.1002/dvdy.1221
|View full text |Cite
|
Sign up to set email alerts
|

zic Gene expression marks anteroposterior pattern in the presumptive neurectoderm of the zebrafish gastrula

Abstract: Anteroposterior (A/P) patterning of the vertebrate neurectoderm begins early during development. In vitro explant assays have been used to show that an A/P subdivision of the zebrafish neurectoderm is in place by early gastrulation. However, no direct markers of this subdivision had been described. We report isolation of two members of the zic gene family, zic2 and zic3, which mark distinct regions in the developing nervous system. zic3 is expressed in early gastrula embryos in a posterior domain, directly dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
69
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(71 citation statements)
references
References 34 publications
2
69
0
Order By: Relevance
“…As a brain dorsal marker gene, zic1 is expressed throughout the dorsal brain and in the optic stalk in wild-type embryo. 41 In 5MO-injected embryos, www.landesbioscience.com Autophagyzic1 expression is enhanced in the whole dorsal brain, particularly in the hindbrain extended posteriorly to the trunk; however, it was reduced in the diencephalon/midbrain and suffused ventrally and backwardly in the whole hindbrain, with poor brain division in the atg5 capped-mRNA-injected embryos. This result is supported by a study which indicated that zebrafish zic1 could control the midline formation and forebrain patterning; zic1 loss of function led to ventralization of the optic vesicle and defects of the forebrain midline in zebrafish embryos.…”
Section: Discussionmentioning
confidence: 99%
“…As a brain dorsal marker gene, zic1 is expressed throughout the dorsal brain and in the optic stalk in wild-type embryo. 41 In 5MO-injected embryos, www.landesbioscience.com Autophagyzic1 expression is enhanced in the whole dorsal brain, particularly in the hindbrain extended posteriorly to the trunk; however, it was reduced in the diencephalon/midbrain and suffused ventrally and backwardly in the whole hindbrain, with poor brain division in the atg5 capped-mRNA-injected embryos. This result is supported by a study which indicated that zebrafish zic1 could control the midline formation and forebrain patterning; zic1 loss of function led to ventralization of the optic vesicle and defects of the forebrain midline in zebrafish embryos.…”
Section: Discussionmentioning
confidence: 99%
“…Extracellular BMP antagonists, such as Noggin, Chordin, and Follistatin, bind to BMPs, render them inactive and, therefore, allow the expression of neural genes, including zic genes (Mizuseki et al, 1998;Gamse and Sive, 2001). Accordingly, zebrafish mutants where BMP signaling levels are altered show that zic gene expression is downregulated by BMP signaling (Grinblat et al, 1998;Rohr et al, 1999;Grinblat and Sive, 2001). Most recently, Tropepe et al…”
Section: Inhibition Of Bmp Signalingmentioning
confidence: 99%
“…They are expressed widely in brain, spinal cord, and eye (Grinblat and Sive 2001;Warner et al 2003;Toyama et al 2004). In chick, Zic2 and Zic3 may also play a role in ear development (Warner et al 2003).…”
Section: Functional Analysis Of Dcnesmentioning
confidence: 99%